Electrical storm in a patient with Charcot-Marie-Tooth disease treated with radiofrequency ablation and subsequent serious complication of implantable cardioverter defibrillator implantation: a case report - Vrtal, Jiří; Plášek, Jiří; Václavík, Jan; Šipula, David; Dodulík, Jozef (European heart journal. Case reports, 2025)
BACKGROUND: Charcot-Marie-Tooth is the most common inherited neuromuscular disorder. Rarely, it can be associated with heart failure and various arrhythmic disturbances. This case illustrates the challenges of making decisions to prevent sudden cardiac death in a patient with Charcot-Marie-Tooth disease. CASE SUMMARY: A 69-year-old male with a history of Type 1A Charcot-Marie-Tooth disease was admitted due to repetitive runs of ventricular tachycardia. Twelve-lead electrocardiogram, echocardiography, selective coronary angiography, and cardiac magnetic resonance did not clarify the cause of the electrical storm. As conservative therapy was not successful, radiofrequency ablation was chosen to treat the electrical storm. After this procedure, implantable cardioverter defibrillator (ICD) was implanted. The follow-up revealed severe perforation by the ventricular lead. An extraction was performed with no complications and a new lead was immediately implanted. The patient remains asymptomatic. Three episodes of non-sustained ventricular tachycardia were recorded during the last follow-up. DISCUSSION: This case illustrates the challenges of making decisions to prevent sudden cardiac death in a patient with Charcot-Marie-Tooth disease after successful ablation for electrical storm. Due to a lack of evidence, atypical origin of arrhythmia, and clinical presentation, we did not consider this as idiopathic arrhythmia and decided to implant an ICD, which was complicated by severe perforation by the lead. Specific recommendations for preventing sudden cardiac death in rare cardiac conditions, such as Charcot-Marie-Tooth disease, still need to be refined.